1992
DOI: 10.1002/anie.199206821
|View full text |Cite
|
Sign up to set email alerts
|

Transition Structures of Hydrocarbon Pericyclic Reactions

Abstract: Twenty-five years after the discovery of a vast class of organic reactions named "pericyclic reactions" by Woodward and Hoffmann, ab initio quantum mechanics provides a detailed analysis of the geometries, energies, and electronic characteristics of the transition structures of these reactions. Common features are found in all these reactions, and generalizations permit prediction of other transition-structure geometries and energies. At the same time, great diversity is observed-from strongly bonded, rigid, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

39
382
0
4

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 638 publications
(425 citation statements)
references
References 240 publications
39
382
0
4
Order By: Relevance
“…Quantum chemical calculations [30][31][32][33][34][35][36][37][38] have confirmed the early predictions based on either just electronic structure considerations or orbital (state) symmetry according to the Woodward-Hoffmann rules.…”
Section: Cycloaddition Of Singlet Methylene To Ethenesupporting
confidence: 56%
See 1 more Smart Citation
“…Quantum chemical calculations [30][31][32][33][34][35][36][37][38] have confirmed the early predictions based on either just electronic structure considerations or orbital (state) symmetry according to the Woodward-Hoffmann rules.…”
Section: Cycloaddition Of Singlet Methylene To Ethenesupporting
confidence: 56%
“…[28][29][30][31][32][33][34][35][36][37][38] Hoffmann and co-workers [29] demonstrated that the reaction of methylene and ethene is symmetry-allowed when the methylene follows a C s symmetrical non-linear (oblique) approach path whereas it is forbidden when the reaction complex possesses C 2v symmetry corresponding to a linear movement of methylene along the C 2 axis of the complex and leading to a T-structure where the top bar is the ethene molecule.…”
Section: Cycloaddition Of Singlet Methylene To Ethenementioning
confidence: 99%
“…Whether conservation of orbital symmetry is important in the chemistry of open shell species is sometimes questioned. A number of 1,3-H-shifts in radical cations have now been characterized by theory, and all of those circumvent pathways that violate conservation of orbital symmetry [19,20,22]. Some of those expend substantial energy to take symmetry-allowed pathways through antarafacial transition states [19], some have transition states at the boundary between being antarafacial and suprafacial (present results), and some utilize subjacent orbitals to take suprafacial pathways (present results).…”
Section: 1mentioning
confidence: 55%
“…Nonetheless 1,3-H-shifts do occur [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], or would were it not for competition from lower energy processes [18 -23]. Theoretical studies conducted since the work of Woodward and Hoffmann show that 1,3-H-shifts across -bonds can be antarafacial [19,20,22], suprafacial [22], or at the boundary between the two such that they are neither antarafacial nor suprafacial [22], a surprising diversity of trajectories.…”
mentioning
confidence: 99%
“…[12][13][14][15] An evidence of the importance of this reaction to the development and application of some computational calculations is the large number of published papers involving considerations about the concerted and nonconcerted, synchronous and asynchronous mechanism nature of some Diels-Alder reactions. [15][16][17][18] Most of these studies attempt to explain some experimental results non-consistent with empirical rules or expected results concerning the selectivity. While experimental measurements can provide accurate rate constants for the different reaction pathways, high-level quantum chemical calculations are often necessary to explain the observed phenomena at an electronic level, to predict the substituent effects and also to evaluate steric interactions between the participating species.…”
mentioning
confidence: 99%